Deep Injection of Waste Water in the Western Canada Sedimentary Basin. Issue 2 (19th May 2014) - Ferguson, Grant
Abstract Injection of wastes into the deep subsurface has become a contentious issue, particularly in emerging regions of oil and gas production. Experience in other regions suggests that injection is an effective waste management practice and that widespread environmental damage is unlikely. Over the past several decades, 23 km3 of water has been injected into the Western Canada Sedimentary Basin (WCSB). The oil and gas industry has injected most of this water but large amounts of injection are associated with mining activities. The amount of water injected into this basin during the past century is 2 to 3 orders magnitude greater than natural recharge to deep formations in the WCSB. Despite this large‐scale disturbance to the hydrogeological system, there have been few documented cases of environmental problems related to injection wells. Deep injection of waste appears to be a low risk activity based on this experience but monitoring efforts are insufficient to make definitive statements. Serious uncharacterized legacy issues could be present. Initiating more comprehensive monitoring and research programs on the effects of injection in the WCSB could provide insight into the risks associated with injection in less developed sedimentary basins.